2011
DOI: 10.4097/kjae.2011.61.6.465
|View full text |Cite
|
Sign up to set email alerts
|

Dilution and slow injection reduces the incidence of rocuronium-induced withdrawal movements in children

Abstract: BackgroundThe aim of this study was to evaluate whether slow injection of diluted rocuronium could reduce rocuronium-induced withdrawal movements effectively in children.MethodsAfter loss of consciousness, rocuronium 0.6 mg/kg was administered into 171 children according to the pre-assigned groups as follows: Group CF, injection of non-diluted rocuronium over 5 seconds; Group CS, injection of non-diluted rocuronium over 1 minute; Group DF, injection of diluted rocuronium (10 times) over 5 seconds; Group DS, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
0
16
1
1
Order By: Relevance
“…Rocuronium has a PH of 4.0, and dilution could reduce injection pain [25], which may explain the injection pain of it [26]. Blunk and Seifert [27] Injecting lidocaine was reported the best intervention to prevent RAIPWR [21], and we found AAs also took effect.…”
Section: Discussionmentioning
confidence: 58%
“…Rocuronium has a PH of 4.0, and dilution could reduce injection pain [25], which may explain the injection pain of it [26]. Blunk and Seifert [27] Injecting lidocaine was reported the best intervention to prevent RAIPWR [21], and we found AAs also took effect.…”
Section: Discussionmentioning
confidence: 58%
“…Thirteen studies mentioned the method of random sequence generation [11,12,13,14,15,16,17,18,19,20,21,22,23], and 10 studies used allocation concealment [11,14,23,24,25,26,27,28,29,30]. Patients were blinded in 39 studies [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49], whereas outcome assessors were blinded in 25 studies [11,12,13,16,17,18,19,20,21,22,23,24,25,27,28,29,30,31,34,35,36,37,38,40,42].…”
Section: Resultsmentioning
confidence: 99%
“…Arndt and Klement [24] reported that peripheral veins were invested with polymodal nociceptors, which released endogenous pain mediators such as prostaglandins after being stimulated by unphysiological osmolarity or pH of drug solution. Rocuronium has a PH of 4.0, and dilution could reduce injection pain [25], which may explain the injection pain of it [26]. Blunk and Seifert [27] demonstrated the dolorific effect of rocuronium may be on account for direct activation of C-nociceptors nerve endings with release of calcitonin prostaglandin (PG) E2 and gene-related peptide (CGRP).…”
Section: Discussionmentioning
confidence: 99%